PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA PADA MATERI PECAHAN SENILAI TERHADAP HASIL BELAJAR SISWA KELAS IV SDN 3 CISAYONG - Nadira Novita Febrianti; N Leni Sri Mulyani; Mohammad Fahmi Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to develop and determine the effectiveness of Canva-based interactive learning media on mathematics learning outcomes for equivalent fractions in grade IV of Elementary School. This is motivated by students' weak understanding of equivalent fractions and the limited use of learning media, necessitating engaging innovations in learning to effectively convey the material. The method used in this research is Research and Development (R&D) with the Born and Gall model, which consists of 10 steps, including identifying potential and problems, data collection, product design, design validation, design improvement, product testing, product revision, usage testing, product revision, and mass production. The subjects in this study include all fourth-grade students at SDN 3 Cisayong. The data in this study were obtained from observation, interviews, expert validation, and student response questionnaires during the trial. The validation results from the experts were 93% from content experts, 100% from language experts, and 93% from media experts, indicating that this media is highly valid and suitable for testing. Based on the results of the effectiveness test research conducted at SDN 3 Cisayong with a total of 20 students, the N-gain score obtained was 0.76 or 76%, categorized as "Effective," with the lowest score being 0.71 or 71% and the highest score being 1 or 100%. Therefore, it can be concluded that the Canva-based interactive learning media is effective for use and can improve the learning outcomes of 4th-grade elementary school students on equivalent fractions. Keywords: Interactive Learning Media, Canva, Equivalent Fractions